2015
DOI: 10.1103/physrevx.5.041030
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Chaos in Random Neuronal Networks

Abstract: Firing patterns in the central nervous system often exhibit strong temporal irregularity and considerable heterogeneity in time-averaged response properties. Previous studies suggested that these properties are the outcome of the intrinsic chaotic dynamics of the neural circuits. Indeed, simplified rate-based neuronal networks with synaptic connections drawn from Gaussian distribution and sigmoidal nonlinearity are known to exhibit chaotic dynamics when the synaptic gain (i.e., connection variance) is sufficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
384
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 175 publications
(410 citation statements)
references
References 58 publications
18
384
0
3
Order By: Relevance
“…Using this connectivity as their basis, a long series of works shows that by careful tampering with such a structure one may achieve a number of useful ends, with a notable flurry of recent activity [23][24][25][26][27][28][29][30][31].…”
Section: Contextmentioning
confidence: 99%
“…Using this connectivity as their basis, a long series of works shows that by careful tampering with such a structure one may achieve a number of useful ends, with a notable flurry of recent activity [23][24][25][26][27][28][29][30][31].…”
Section: Contextmentioning
confidence: 99%
“…It is generally accepted that the inherent instability of chaos in 4 nonlinear systems dynamics, facilitates the extraordinary ability of neural systems to 5 respond quickly to changes in their external inputs [3], to make transitions from one 6 pattern of behavior to another when the environment is altered [4], and to create a rich neurons [3,[13][14][15][16][17][18][19][20][21]. The first type of chaotic dynamics in neural systems is typically 14 accompanied by microscopic chaotic dynamics at the level of individual oscillators.…”
mentioning
confidence: 99%
“…Synchronous chaos has been demonstrated in networks of 18 both biophysical and non-biophysical neurons [3,13,15,17,[22][23][24], where neurons display 19 synchronous chaotic firing-rate fluctuations. The latter cases, the chaotic behavior is a 20 result of network connectivity, since isolated neurons do not display chaotic dynamics or 21 burst firing. More recently, a totally different mechanism showed that asynchronous 22 chaos, where neurons exhibit asynchronous chaotic firing-rate fluctuations, emerge 23 generically from balanced networks with multiple time scales synaptic dynamics [20].…”
mentioning
confidence: 99%
See 2 more Smart Citations